Analisis Good Corporate Governance, Media Exposure, Profitabilitas dan Pengaruhnya Terhadap Pengungkapan Emisi Karbon - Dyah Aruning Puspita; Melani Ariya Tanjaya (Bulletin of Management and Business, 2022)
The purpose of this study was to determine the effect of media exposure, profitability and corporate governance on the carbon emission disclosure. In this research , the population used is all mining companies listed on the IDX in 2018-2020. By using the sample criteria obtained 30 companies as research samples. It is known from the research result that corporate governance as proxy the size of board of commissioners has no effect on the carbon emission disclosure, while the proxy of the audit committee also has no effect on the disclosure on the carbon emission disclosure. Media exposure has significant positive effect on the carbon emission disclosure. And profitability has a significant positive effect on the carbon emission disclosure.